NEW NORMAL LEARNING EFFECTIVENESS IN INFORMATION AND COMMUNICATION TECHNOLOGY SUBJECTS - Edy Susanto; Fadlul Amdhi Yul; Melo Trisa Putra; Jumiati Siska (Journal Of Dehasen Educational Review, 2021)
The goal of this study was to describe the efficacy of new normal learning in the subject of information and communication technology in class X State High School 8 in Bengkulu city. This is a qualitative research method. Interviews, observation, and documentation studies were used to collect data for this study. The study's findings include effective learning using the lecture method, learning implementation that is faster than before, making learning implementation plans in the new normal in accordance with government guidelines, and learning that is less effective due to limited time, resulting in less than optimal learning. Applications of this study: This study is beneficial to Bengkulu City 8 State High School, which is learning in the new normal era. Researchers are interested in the effectiveness of new normal learning at the high school level in Bengkulu City. It can provide input to stakeholders by examining the effectiveness of new normal learning in Bengkulu City 8 State High School. It is necessary to conduct additional research in order for this research to progress. This is a new science for State High School 8 in Bengkulu City.